Bioavailability of Vitamin D in Malnourished Adolescents with Anorexia Nervosa - DiVasta, Amy D. (Endocrine Society, 2011)
CONTEXT: Young women with anorexia nervosa (AN) have a normal vitamin D status. The bioavailability of vitamin D during malnutrition is unknown. OBJECTIVE: The objective of the study was to examine the serum response to oral ergocalciferol in AN. DESIGN/SETTING: This was a prospective cohort study, conducted in 2007–2009 at a tertiary care center. PATIENTS/INTERVENTIONS: Twelve adolescents with AN (age 19.6 ± 2.0 yr, body mass index 16.5 ± 1.4 kg/m(2)) and 12 matched healthy controls (20.0 ± 2.4 yr, 22.7 ± 1.0 kg/m(2)) received one baseline 50,000 IU oral dose of ergocalciferol. MAIN OUTCOMES: Serum D(2), D(3), 25-hydroxyvitamin D, and 1,25-dihydroxyvitamin D, collected before ingestion, at 6 and 24 h and weekly for 4 wk, and body composition measures were measured. RESULTS: The AN group was severely malnourished (77.2 ± 6.3% median body weight), whereas the control group was normal weighted (106.2 ± 6.2%). From a common baseline D(2) (1.5 ± 1.6 nmol/liter, P =0.34) the groups diverged (time × group interaction P = 0.04), peaking at 70 ± 34 nmol/liter at 6 h in controls compared with 43 ± 28 nmol/liter in AN subjects (P = 0.008). The D(2) trajectories converged at 24 h (57 nmol/liter, P = 0.98) and returned to near baseline at 1 wk. Baseline D(3) was higher in AN subjects (12.1 ± 9.6 vs. 3.1 ± 2.3 nmol/liter, P < 0.001) and remained higher throughout. 25-Hydroxyvitamin D followed a common trajectory (time × group interaction P = 0.15), rising to 45 ± 10 nmol/liter at 24 h but returning to baseline by wk 3 (P = 0.36). Correlating vitamin D levels with fat measures (body mass index, body fat) produced similar findings. CONCLUSIONS: Despite severe malnutrition, young women with AN had a similar bioavailability of oral ergocalciferol as the healthy-weighted controls. Vitamin D dosing for patients suffering from malnutrition may not differ from that for normal-weighted adolescents.